2015
DOI: 10.1016/j.euroneuro.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The oxytocin analogue carbetocin prevents priming-induced reinstatement of morphine-seeking: Involvement of dopaminergic, noradrenergic and MOPr systems

Abstract: Total word-count: 2488 words 2 ABSTRACTRelapse to illicit drug-seeking following abstinence is a major challenge for the treatment of addiction as no effective pharmacotherapy is currently available. We have recently shown that activating the central oxytocinergic system prevents emotional impairment and stress-induced reinstatement associated with opioid withdrawal. Here, we investigated whether the oxytocin analogue carbetocin (CBT) is able to reverse morphine-primed reinstatement conditioned place preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 17 publications
4
29
0
1
Order By: Relevance
“…Furthermore, no studies have been published showing that oxytocin impacts heroin reinstatement. Related, carbetocin, an oxytocin analogue, reduced stress-induced (Zanos et al, 2014) and drug-primed (Georgiou et al, 2015) reinstatement of morphine-seeking. Preliminary data from our laboratory (Fig.…”
Section: Oxytocin Effects On Preclinical Models Of Addictionmentioning
confidence: 99%
“…Furthermore, no studies have been published showing that oxytocin impacts heroin reinstatement. Related, carbetocin, an oxytocin analogue, reduced stress-induced (Zanos et al, 2014) and drug-primed (Georgiou et al, 2015) reinstatement of morphine-seeking. Preliminary data from our laboratory (Fig.…”
Section: Oxytocin Effects On Preclinical Models Of Addictionmentioning
confidence: 99%
“…Trunk blood from saline-and METH-treated/withdrawn mice was collected in EDTA-containing tubes and spun for 15 min at 2000 x g at 4 o C. Plasma was collected and corticosterone levels were measured using a rat/mouse corticosterone [ 125 I] kit (MP Biomedicals, USA), according to the manufacturer's instructions; also see Georgiou et al (2015b).…”
Section: Plasma Corticosterone Levels (Experiments 3)mentioning
confidence: 99%
“…Similarly, in humans, carbetocin had a prolonged effect on post‐partum uterine activity in terms of both a higher amplitude and frequency of contractions compared to oxytocin . Concerning the central effects of carbetocin, studies in rodents demonstrated that carbetocin reduced anxiety‐like behaviours in the elevated plus maze test , had antidepressant‐like effects in the forced swimming test and attenuated the negative emotional consequences of opioid withdrawal .…”
mentioning
confidence: 99%